2003
DOI: 10.1117/1.1557693
|View full text |Cite
|
Sign up to set email alerts
|

Noise modeling of an InP/InGaAs heterojunction bipolar phototransistor

Abstract: We present a theoretical analysis of the noise behavior of a heterojunction bipolar transistor (HBT) used as a three terminal (3T) photodetector. The use of a HBT in the photodetector mode can greatly simplify the fabrication of HBT-based optical receivers in the monolithic form. The present model takes into account the effect of the received light on the intrinsic parameters and various noise components of the HBT when used as a detector. The model enables one to determine the signal-to-noise ratio at the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In our work [13] Unfortunately, however, no data for GBW and SNR for InGaAs-based HPT are available for the structure we have considered in this work. Chakrabarti et al [12] presented the values of GBW and SNR for HPTs with InGaAs as the base. Both the works [12,13] rely on the theory developed in [9].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our work [13] Unfortunately, however, no data for GBW and SNR for InGaAs-based HPT are available for the structure we have considered in this work. Chakrabarti et al [12] presented the values of GBW and SNR for HPTs with InGaAs as the base. Both the works [12,13] rely on the theory developed in [9].…”
Section: Resultsmentioning
confidence: 99%
“…The noise equivalent circuit considered in this work has been developed by Chakraborti et al [12] and is shown in Fig. 2.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations